Juridical Implications of Constitutional Court Decision Number 78/PUU-XXI/2023 on Freedom of Expression in Indonesia - Jaya, I Putu Agus Kusuma; Windari, Ratna Artha; Ardhya, Si Ngurah (International Journal of Business, Law, and Education, 2026)
Freedom of expression constitutes a constitutionally protected right under the 1945 Constitution of the Republic of Indonesia. Nevertheless, its implementation continues to encounter significant challenges, particularly due to the existence of vague criminal provisions that generate legal uncertainty and create the risk of criminalizing legitimate expressions. This issue became central to the judicial review of Articles 14 and 15 of Law Number 1 of 1946 concerning Criminal Law Regulations, culminating in Constitutional Court Decision Number 78/PUU-XXI/2023. This study aims to examine the Constitutional Court’s legal reasoning and to analyze the juridical implications of the decision for the protection of freedom of expression in Indonesia. Employing normative legal research, this study applies statutory, conceptual, and case approaches. The analysis is conducted qualitatively on primary, secondary, and tertiary legal materials. The findings indicate that the Court emphasized that any restriction on freedom of expression must meet the requirements of clarity, precision, and proportionality. The Court held that ambiguous criminal norms violate the principles of legal certainty (lex certa) and constitutional protection of rights. Consequently, the Court declared the contested provisions unconstitutional and legally non-binding. The decision establishes a constitutional benchmark for assessing other restrictive criminal norms, including those contained in the new Criminal Code and the amended Electronic Information and Transactions (EIT) Law. Thus, the ruling reinforces constitutional safeguards for freedom of expression and provides normative guidance for legislators and law enforcement authorities in formulating and implementing criminal law policies.